(untitled) (BioLaw Journal - Rivista di BioDiritto, 2022)
The paper reports a speech carried out during a meeting regarding the draft law on medically assisted death. In addition to the criticisms of the text, it is proposed the possibility to insert the regulation within the law 219/2017, in order to reframe assisted death as part of medical treatments and the doctor-patient relationship.